Peran Kader memberikan Edukasi Gizi pada Kegiatan Posyandu - Ravi Masitah; Putri Sinta Maharani; Amelia Prahastuti; Nessy Iqmadhea (IKesT Muhammadiyah Palembang, 2023)
Posyandu is a public health service. Posyandu activities involve various parties such as health workers, the community and community leaders. Kader are people who are given various training by health workers to be able to help provide health information to the community. The activeness of kader can influence the motivation of mothers to come to the posyandu to monitor the health and nutrition of mothers and children. The research was carried out in the Kuto Batu Village, Palembang in August 2022. The research subjects were kader at 12 posyandu in the Kuto Batu Village. The results showed that most of the kader had provided nutrition education at posyandu activities, although this was not always the case. However, there are still kader who are not active in providing nutrition education to the community. Therefore it is necessary to make efforts to increase the role of kader, especially in terms of providing nutrition education to the community through training, seminars and workshops.